Biochar Effects on Weed Management - Neeta Soni; Jason A. Ferrell; Pratap Devkota; Michael J. Mulvaney (EDIS)
This publication provides an overview of the impact of biochar use as a soil amendment on weed management. Written by Neeta Soni, Jason A. Ferrell, Pratap Devkota, and Michael J. Mulvaney, and published by the UF/IFAS Agronomy Department, revised May 2021.